Efektifitas Layanan Konseling Kelompok Dengan Pendekatan Behevioral Teknik Relaksasi Untuk Mengatasi Kejenuhan Belajar Siswa - Rudi Hartono; Mhd Subhan (Fakultas Tarbiyah dan Keguruan, 2020)
This research aimed at knowing how effective group counseling service with behavioral approach to relaxation technique in overcoming student learning saturation. Pre-experimental research method was used in this research with Pretest Posttest One Group design. The subjects were the students experiencing highlearning saturation, and the object was group counseling service with behavioral approach to relaxation technique in overcoming student learning saturation. Questionnaire, observation, and documentation were the techniques of collecting the data. Pearson product moment was used for questionnaire validity test and Alpha Cronbach was used for reliability test. The data analysis that was Wilcoxon test was used to know whether group counseling service with behavioral approach to relaxation technique could be implemented in overcoming student learning saturation. The research findings showed the mean score of student learning saturation before being given treatment group counseling service with behavioral approach to relaxation technique 68.4, and the mean score was 48.4. It could that relaxation technique could be implemented in overcoming student learning saturation.